2023
DOI: 10.3390/cells12060853
|View full text |Cite
|
Sign up to set email alerts
|

Current Advancements in Spinal Cord Injury Research—Glial Scar Formation and Neural Regeneration

Abstract: Spinal cord injury (SCI) is a complex tissue injury resulting in permanent and degenerating damage to the central nervous system (CNS). Detrimental cellular processes occur after SCI, including axonal degeneration, neuronal loss, neuroinflammation, reactive gliosis, and scar formation. The glial scar border forms to segregate the neural lesion and isolate spreading inflammation, reactive oxygen species, and excitotoxicity at the injury epicenter to preserve surrounding healthy tissue. The scar border is a phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 155 publications
0
34
0
Order By: Relevance
“…SCI constitutes a complex tissue injury, resulting in permanent and degenerative damage to the CNS. Following SCI, deleterious cellular processes ensue, including axonal degeneration, neuronal loss, neuroinflammation, reactive gliosis, and scar formation ( Clifford et al, 2023 ). The inability of the adult mammalian CNS to regenerate post-injury is the direct cause of the permanent loss of sensory and motor functions following SCI ( Noristani, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…SCI constitutes a complex tissue injury, resulting in permanent and degenerative damage to the CNS. Following SCI, deleterious cellular processes ensue, including axonal degeneration, neuronal loss, neuroinflammation, reactive gliosis, and scar formation ( Clifford et al, 2023 ). The inability of the adult mammalian CNS to regenerate post-injury is the direct cause of the permanent loss of sensory and motor functions following SCI ( Noristani, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The polarization state and other characteristics of macrophage populations recruited into the injured spinal cord were studied by immunohistochemical analysis [ 66 ]. Previous studies [ 89 , 90 , 91 , 92 , 93 , 94 , 95 ] indicated that in spinal cord injuries, M1 macrophages facilitate phagocytosis and secrete pro-inflammatory cytokines such as interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α). These macrophages perform cell debris clearance, and their persistence can also lead to cell death and axonal dieback through increased reactive oxygen species (ROS) generation.…”
Section: Nerve Regeneration In Injured Spinal Cord By α-Gal Nanoparti...mentioning
confidence: 99%
“…Thus, this treatment enables the localized production of VEGF for several weeks, thereby ensuring prolonged enhancing effects on axonal ingrowth into the lesion. In view of the multiple neurotrophins produced by M2 macrophages [ 18 , 94 , 95 , 96 , 97 , 98 , 99 ], it will be of interest to determine whether the M2 macrophages that mediate axonal regeneration in SCI lesions treated with α-gal nanoparticles also produce these neurotrophins at the injection sites.…”
Section: Nerve Regeneration In Injured Spinal Cord By α-Gal Nanoparti...mentioning
confidence: 99%
“…During this injury-induced spike in proliferative activity, NSC progeny migrate towards the injury site, where they continue to proliferate and subsequently differentiate into reactive astrocytes, contributing to the formation of the glial scar (Nicaise et al, 2022), sealing the injury site and limiting secondary injury effects to protect surrounding healthy tissue. The glial scar constitutes a key barrier to outgrowing axons from the injured pathways from reconnecting with their original targets, limiting functional recovery (Bradbury & Burnside, 2019;Clifford et al, 2023;Leal-Filho, 2011;McDonough & Martínez-Cerdeño, 2012;Meletis et al, 2008;Moreno-Manzano, 2020;Nicaise et al, 2022;Tran et al, 2022). Microenvironmental injury sequelae to SCI with compression injuries which leave the dural sack intact, and burst fracture injuries, which induce dural laceration and subsequent intradural decompression, may not be identical.…”
Section: Introductionmentioning
confidence: 99%